Idiopathic paroxysmal kinesigenic dyskinesia in Malaysia, a multi-racial Southeast Asian country - Tai, Mei-Ling.S.; Lim, Shen-Yang; Tan, C.T. (Elsevier, 2010)
Paroxysmal kinesigenic dyskinesia is a rare disorder, and there are few reports of Asian patients with this condition. We reviewed the clinical features of all patients with idiopathic paroxysmal kinesigenic dyskinesia (PKD) seen at a major neurological centre in Malaysia. The charts of 11 patients with idiopathic PKD seen between 1995 and 2008 were reviewed retrospectively. The male:female ratio was 9:2. Ten patients were of Chinese ethnicity, and one was Malay. Three patients (from two families) had a family history of PKD. The involuntary movement was dystonia in 73% of patients. In one patient, attacks were precipitated by vestibular stimulation. One patient had generalized epilepsy. Another patient who did not have epilepsy demonstrated epileptiform discharges. Only slightly over one-quarter of patients had a positive family history. Males, and people of Chinese ancestry, seem to be affected more frequently by MD in certain Asian populations. (C) 2010 Elsevier Ltd. All rights reserved.